How does climate change affect poor people in Africa? - Azzarri, Carlo; Signorelli, Sara; Dawson, Seda; Woodruff, Lisa (Science Journal for Kids, 2020)
Our planet is warming up! That doesn’t mean we will have nicer weather, though. It means we have weather events that are more extreme. Floods, droughts, and heatwaves are more powerful and are happening more often. People lose their homes, jobs, and eat less food. And poor people suffer the most! People who are very poor do not have enough resources to handle the effects of extreme weather events. To help them in the future, we need a good understanding of what is happening now.